The Differential Effects of Anger on Trust: A Cross-Cultural Comparison of the Effects of Gender and Social Distance - Zhang, Keshun; Goetz, Thomas; Chen, Fadong; Sverdlik, Anna (Frontiers in Psychology, 2020)
Accumulating empirical evidence suggests that anger elicited in one situation can influence trust behaviors in another situation. However, the conditions under which anger influences trust are still unclear. The present study addresses this research gap and examines the ways in which anger influences trust. We hypothesized that the social distance to the trustee, and the trusting person’s gender would moderate the effect of anger on trust. To test this hypothesis, a study using a 2 (Anger vs. Control) × 2 (Low vs. High social distance) × 2 (Men vs. Women) factorial design was conducted in Germany (N = 215) and in China (N = 310). Results reveal that in both countries men’s trust behavior was not influenced by the manipulations (i.e., anger and social distance). The pattern for women, however, differed by country. In Germany, women’s trust to a stranger (i.e., high social distance) was increased by anger; while in China, women’s trust to someone who they have communicated with (i.e., low social distance) was increased by anger. These results indicate that women’s trust levels seem to be more context-sensitive than men’s.